Effect of process parameters on hydrothermal liquefaction of oil palm biomass for bio-oil production and its life cycle assessment - Chan, Y.H. (Elsevier Ltd, 2015)
This paper presents the studies on the effect of three process parameters; temperature, pressure and reaction time on the subcritical and supercritical hydrothermal liquefaction of oil palm empty fruit bunch, palm mesocarp fiber and palm kernel shell. The effect of temperature (330-390 °C), pressure (25-35 MPa) and reaction time (30-240 min) on bio-oil yields were investigated using a Inconel batch reactor. The optimum liquefaction condition for empty fruit bunch, palm mesocarp fiber and palm kernel shell was at supercritical condition of water; 390 °C and 25 MPa. For the effect of reaction time, bio-oil from empty fruit bunch and palm mesocarp fiber attained maximum yields at 120 min, whereas bio-oil yield from palm kernel shell continued to increase at reaction time of 240 min. Lastly, a life cycle assessment based on a conceptual biomass hydrothermal liquefaction process for bio-oil production was constructed and presented. © 2015 Elsevier Ltd.